SOCIAL EQUITY IN REGIONAL DEVELOPMENT PLANNING: WHO PLANS FOR REMOTE COMMUNITIES? - Harwood, Sharon; Prideaux, Bruce; Schmallegger, Doris (The journal of contemporary issues in business and government, 2011)
This paper examines the extent to which the concept of social equity was considered in the creation of Regional Development Australia’s Far North Queensland and Torres Strait (RDA FNQTS) Regional Roadmap. The research applies Rawls’ (1973) concept of social equity to determine the extent to which the disparities experienced by the least advantaged populations in the planning area were considered in the regional planning process. The results indicate that decision making was concentrated in the urban core and that the concept of social equity was not embodied in the plan outcomes. The paper concludes that ignoring social equity issues in regional planning has enduring ramifications for remotely located spatial territories where a significant proportion of the population is both Indigenous and disadvantaged.